2002
DOI: 10.1096/fj.01-0825fje
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C matters: increased oxidative stress in cultured human aortic endothelial cells without supplemental ascorbic acid

Abstract: Because standard culture media for human aortic endothelial cells (HAEC) do not contain vitamin C, we hypothesized that HAEC may be under significant oxidative insult compared with the situation in vivo. To assess parameters of oxidative stress, intracellular vitamin C, glutathione (GSH), GSH/GSSG, and NAD(P)H/NAD(P)+ ratios, as well as oxidant appearance and oxidative damage, were measured in HAEC with or without vitamin C addition. The effect of vitamin C on eNOS activity was also determined. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 56 publications
3
51
0
Order By: Relevance
“…It is hydrophilic and can directly scavenge ROS and lipid hydroperoxides. Vitamin C can also restore oxidized vitamin E and can spare selenium [131]. Carotenoids, such as -carotene are lipid soluble antioxidants that function as efficient scavengers of 1 O2 but may also quench ROO .…”
Section: Non-enzymatic Antioxidants Defensesmentioning
confidence: 99%
“…It is hydrophilic and can directly scavenge ROS and lipid hydroperoxides. Vitamin C can also restore oxidized vitamin E and can spare selenium [131]. Carotenoids, such as -carotene are lipid soluble antioxidants that function as efficient scavengers of 1 O2 but may also quench ROO .…”
Section: Non-enzymatic Antioxidants Defensesmentioning
confidence: 99%
“…Prior to experiments, cells were incubated in freshly made 60 μM BH 4 for 10 min to compensate for variable cell culture-induced BH 4 deficiencies (13)(14)(15). Experimental results in the absence of an initial BH 4 supplementation were qualitatively identical but with lower NO• production, suggesting that pretreatment was not likely to affect the interpretation of the results.…”
Section: Cell Treatmentsmentioning
confidence: 99%
“…In this context, antioxidants may play important roles, although the literature so far shows conflicting results. Ascorbic acid has been shown to increase both glutathione (GSH) and NOS activity in human endothelial cells (Smith et al 2002), and the effect seems to be due to stabilization of the BH4 molecule (Werner et al 2003). Glutathione is a major cellular redox determinant, but some investigators have indicated that glutathione does not seem to have significant impact on the NOS (Huang et al 2001), while others have indicated a correlation between GSH level and NOS activity (Laursen et al 2001;Smith et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid has been shown to increase both glutathione (GSH) and NOS activity in human endothelial cells (Smith et al 2002), and the effect seems to be due to stabilization of the BH4 molecule (Werner et al 2003). Glutathione is a major cellular redox determinant, but some investigators have indicated that glutathione does not seem to have significant impact on the NOS (Huang et al 2001), while others have indicated a correlation between GSH level and NOS activity (Laursen et al 2001;Smith et al 2002). Novel findings have suggested a regulatory role of glutathione in glutathiolating specific proteins at specific residues; the reversible glutathiolation may thus protect these otherwise reactive sites against irreversible oxidation (West et al 2006).…”
Section: Introductionmentioning
confidence: 99%